A perspective on cellulose dissolution with deep eutectic solvents - Alsoy Altinkaya, Sacide (Frontiers in Membrane Science and Technology, 2024)
Currently, membrane manufacturing relies heavily on fossil-based solvents and polymers, resulting in significant negative impacts on human health and the environment. Thus, there is an urgent need for eco-friendly, low-toxicity, and sustainable solvents and polymers to comply with the United Nations' sustainable development goals. Cellulose, as a green, natural, and abundant polymer, offers a sustainable source for membrane manufacturing. However, a significant challenge exists in dissolving cellulose due to strong intermolecular and intramolecular hydrogen bonds within cellulose molecules. Deep eutectic solvents (DESs), which contain both hydrogen bond donor and acceptor groups, have received significant attention as alternative solvents for cellulose dissolution owing to their low cost, low toxicity, environmentally friendly nature, ease of synthesis, and versatility. This review examines experimental studies, and theoretical approaches, highlighting key findings and factors influencing cellulose dissolution in deep eutectic solvents.